Research Mapping of “Intellectual Property Law”: A Bibliometric Visualization Analysis Based on the Scopus Database from 2000 to 2023 - Poologanathan, P. (University Librarians Association of Sri Lanka, 2025)
This study aims to provide a comprehensive bibliometric mapping of global research trends in Intellectual Property Law (IPL) from 2000 to 2023, using data extracted from the Scopus database. Despite IPL's critical role in regulating creativity, innovation, and knowledge dissemination, especially in the digital age, there has been limited bibliometric synthesis of its scholarly landscape. This research addresses that gap by systematically analyzing 801 documents using VOSviewer, Biblioshiny and Microsoft Excel to uncover conceptual structures, collaborative networks, and thematic evolutions within the field. The analysis covered publication output by country and breakdowns by journal, institution, subject, keywords, citations, documents, and author. In total, 801 publications were published with 3,824 citations in the past 23 years. Co-authorship analysis highlights fragmented collaboration, with limited international cooperation outside high-income countries, particularly the USA and the UK. Influential authors and journals include institutions such as Harvard University and journals like the Journal of IPL & Practice. Keyword co-occurrence patterns suggest growing attention to terms such as "innovation," "digital economy", and "intellectual property", pointing to shifts in the legal discourse around emerging technologies. The USA produced the highest number of publications, 196 (24%), while the maximum number of publications was published in 2020 and 2021 with 47 records (6%). It was also found that the most commonly used keyword is Intellectual Property 138 (17%) in the publication on IPL. This bibliometric mapping contributes to the Library and Information Sciences (LIS) field by offering a knowledge structure of IPL that supports evidence-based collection development, scholarly communication services, and policy formulation related to digital rights and access to knowledge.
Keywords: Intellectual Property; Law; Human Mind; Property Rights; Intangible Assets; Bibliometric